Peran Hukum Dalam Menjamin Kesetaraan Gender Di Tempat Kerja - Daya, Feditina (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2024)
This study aims to examine the effect of the Direct Instruction learning model on students' learning outcomes in the material of environmental conservation procedures in building construction work. The research method used is a quasi-experiment with a non-equivalent control group design. The research sample consists of two classes, each serving as the experimental and control groups, selected using purposive sampling. The research instrument is a learning outcome test in the form of multiple-choice questions, which have been tested for validity and reliability. The results of data analysis show that there is a significant improvement in students' learning outcomes in the experimental class compared to the control class. The application of the Direct Instruction model has proven to be effective in helping students understand the concepts, steps, and procedures of environmental conservation related to building construction work. This study recommends the use of the Direct Instruction model as one alternative learning strategy to improve learning outcomes in construction engineering subjects.